Pre-eclampsia and the risk of retinopathy of prematurity in preterm infants with birth weight <1500 g and/or <31 weeks' gestation. Issue 1 (19th June 2017) - Alshaikh, Belal; Salman, Omar; Soliman, Nancy; Ells, Anna; Yusuf, Kamran
Abstract : Objective: To evaluate the relationship between pre-eclampsia and development of retinopathy of prematurity (ROP) in infants with birth weight of <1500 g and/or gestation <31 weeks. Methods: A retrospective cohort study comprising infants born to mothers with pre-eclampsia between January 2007 and June 2010 at a single tertiary care centre. Their ROP outcome was compared with infants born to the next two normotensive mothers with a ±1 week gestational age difference. Pearson χ 2 test was used for categorical variables and Mann-Whitney U test was used for continuous variables. Multivariable regression was used to estimate the OR of ROP with prenatal pre-eclampsia exposure and adjust for confounders. Results: Of the 97 infants in the pre-eclampsia group, 27 (27%) developed ROP and of the 185 infants in the normotensive group, 50 (27%) developed ROP. On multivariable regression modelling, pre-eclampsia was not a risk factor for the development of ROP (OR 1.4, 95% CI 0.46 to 4.1). Gestational age, intrauterine growth restriction and blood transfusion were significant risk factors for the development of ROP. Conclusions: In our cohort, pre-eclampsia was not a significant risk factor for the development of ROP. Intrauterine growth restricted infants of pre-eclamptic and normotensive mothers were at higher risk of ROP.